Evaluating the English version of the novel “Beloved Oxford” = Đánh giá bản dịch Việt - Anh tác phẩm “Oxford thương yêu” . M.A Thesis Linguistics: 60 22 15 - Trần, Thanh Hương (University of Languages and International Studies, 2017)
M.A. Thesis English Linguistics -- University of Languages and International Studies. Vietnam National University, Hanoi, 2012